PERAN TOKOH ADAT DALAM MENGATASI KENAKALAN REMAJA DI DESA SEMELINANG TEBING KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Okta Nilma Diala Sari; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in the village of Semelinang TebingSubdistrict Peranap Indragiri Hulu Regency. The purpose of this research is tofind out what causes the onset of juvenile delinquency, as well as knowing how toanalyse the role of indigenous leaders in completing of juvenile delinquency inthe village of Semelinang Tebing Subdistrict Peranap Indragiri Hulu Regency.The technique of determination of the sample are purposive sampling because theauthor has set some criteria for the subject to be used as a source of informationin the research that will be conducted as many as 8 (eight) people. The authoruses descriptive qualitative methods and instrument data are observation,interview and documentation. The results of research to find the causes of theoccurrence of juvenile delinquency could come from inside of teens and teen selffrom the outside. Which aspects influenced the occurrence of juvenile delinquencyin adolescence here is in the form of an identity crisis and a weak self control aswell as the age that is still relatively vulnerable in doing any violation and crime.Lack of knowledge about religion and manners are sublime. So the lack of selfcontrol in children. Causes of adolescent self from the outside that is either a lackof attention from parents, family, economic factors influence the environmentaround peers and the mass media. The absence of a parent control causes moreand make it easier for children to do at will. Types of juvenile delinquencyhappening such as stealing and doing sex outside marriage so unsettling society.Custom character roles in resolving the problem of juvenile delinquency is to giveadvice, provide knowledge or understanding, provide direction and guidance andprovide solutions. The process of solving problems had levels ranging from thelowest level to the top level. resolved according to customary system used in thevillage of Semelinang Tebing.Key Words: Role, Indigenous Leaders, Juvenile Delinquency